Sex differences in lipids: A life course approach - Holven, Kirsten B.; Roeters van Lennep, Jeanine (Atherosclerosis, 2023)
Differences between men and women in lipids and lipoproteins are observed in distribution and trajectory from infancy to adulthood in the general population. However, these differences are more pronounced in hereditary lipid disorders such as familial hypercholesterolemia (FH) when absolute cholesterol levels are higher from birth onwards. In the early life course, girls compared to boys have higher low-density lipoprotein cholesterol (LDL-C) levels and total cholesterol, while high-density lipoprotein cholesterol (HDL-C) levels are similar. In early adulthood to middle-age, women have lower LDL-C and higher HDL-C levels, as LDL-C levels increase and HDLC levels decrease in men. In the elderly, all lipids – total cholesterol, LDL-C, HDL-C and triglyceride levels decrease but are more pronounced in men. Lipid levels are also affected by specific transitions in girls/women such as the menstrual cycle, pregnancy, breastfeeding and menopause. Lipid levels fluctuate during the menstrual cycle. During pregnancy a physiological increase of LDL-C and even a larger increase in triglyceride levels are observed. Pregnancy has a double impact on LDL-C accumulation in women with FH as they have to stop statins, and the absolute increase in LDL-C is higher than in women without FH. In the menopausal transition, women develop a more adverse lipid profile. Therefore, it is important to take into account both sex and the life course when assessing a lipid profile. [Display omitted] •Women are characterized by a more atherogenic lipid profile from infancy to early adulthood and from middle age to old age.•Transition periods in women, such as menstrual cycle, pregnancy, breastfeeding and menopause, influence lipid levels.•The sex difference and the effect of the female transition periods seem to be more pronounced in women with FH.